Katolickie Towarzystwo Robotników Polskich w Poznaniu „przy Farze"1 w latach 1893-1904 pod patronatem ks. Antoniego Stychla - Taisner, Remigiusz (Ecclesia. Studia z Dziejów Wielkopolski, 2010)
The article presents the activity of Rev. Antoni Stychel in the Catholic Society of Polish Workers , At the Main Parish Church" (Fara) in Poznań in the years 1893-1904. When assuming the position of patron in the society of workers, Stychel already had the experience of work with craftsmen. The statutes that he wrote for the workers were modeled on those for the craftsmen's association. Their careful analysis shows that the changes introduced by him, mostly minor ones, resulted from his experiences during his work with the craftsmen. The ideas which emerged in the course of his work with the craftsmen and turned out to contribute to their development were also incorporated by him in his ministry to the workers. Similarly as before, also in the latter case he organized talks, presentations and social gatherings. He was concerned for the workers' development not only in the religious sphere but also in the area of culture and education. In his ministry among the workers he realized those ideas which he could not previously put into practice with the craftsmen due to a lack of time or possibilities - provident societies and funeral funds were established in order to strengthen the workers and ensure them a worthy life in the hard times they had to live in.